Salzburg, Austria - Homann, Johann Baptista, 1664-1724 (cartographer):::Creator:::::::::::: (Nuremburg; Germany)
Map of Salzburg, Austria, from the 18th century, possibly printed in the early 19th century, with a portrait of Archbishop of Salzburg surrounded by angelic and allegorical figures.